THE DEVELOPING OF MODUL ON SCIENCE SCHOOL MATERIAL WITH PANCASILA CHARACTER - Mukhammad Aji Fatkhurrohman; Wahyu Jati Kusuma (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2019)
The characteristics of the Pancasila values of the younger generation in the present era are depleting. This can be seen from the emergence of cases that occur now, from radical understanding to the Caliphate. The results of the Republic of Indonesia's National Police study stated that many students were involved in radical groups, generally science students. In this regard, efforts need to be made to improve the characteristics of Pancasila in science students. The purpose of this study is to develop, determine validity, and the level of readability of the School Science Material study module characterized by Pancasila. This research is a development research. The research subject was the science education student at Pancasakti University Tegal. The research steps include needs analysis, development stage, the process of making the School Science Material Study module characterized by Pancasila, validation by validator, evaluation, and refinement, product testing, final product module, School Science Material Study, characterized by validity and readability. Validation was done with an expert validator. Limited scale testing is used to test the level of readability. The results of the research in the form of the development of the School Science Material Study module characterized by Pancasila, the subject of Electricity and Magnetism, which has high validity and an easily understood level of readability.